2018
DOI: 10.1371/journal.pone.0208928
|View full text |Cite
|
Sign up to set email alerts
|

Livestock management, beaver, and climate influences on riparian vegetation in a semi-arid landscape

Abstract: Riparian and aquatic habitats support biodiversity and key environmental processes in semi-arid and arid landscapes, but stressors such as conventional livestock grazing, wildfire, and drought can degrade their condition. To enhance habitat for fish and wildlife and increase resiliency in these critical areas, land managers in the interior western United States increasingly use alternative grazing strategies, beaver management, or beaver dam surrogates as low-effort, low-expense restoration approaches. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 93 publications
3
27
0
Order By: Relevance
“…Several studies identify changes such as increased surface water, higher groundwater levels, improved stream conditions, and increased riparian vegetation that are at least partially attributable to the increase in beaver dams that has occurred in Elko County stream systems since the early 1990s. Additionally, research from Elko County and watersheds in southeastern Oregon documents the positive response of riparian vegetation along low-gradient streams to a combination of conservation grazing practices and beaver dam development, with benefits for fish and wildlife (Fesenmyer et al 2018). These documented changes are consistent with the observations of interviewees.…”
Section: Consequences Of Beaver Colonizationsupporting
confidence: 63%
See 1 more Smart Citation
“…Several studies identify changes such as increased surface water, higher groundwater levels, improved stream conditions, and increased riparian vegetation that are at least partially attributable to the increase in beaver dams that has occurred in Elko County stream systems since the early 1990s. Additionally, research from Elko County and watersheds in southeastern Oregon documents the positive response of riparian vegetation along low-gradient streams to a combination of conservation grazing practices and beaver dam development, with benefits for fish and wildlife (Fesenmyer et al 2018). These documented changes are consistent with the observations of interviewees.…”
Section: Consequences Of Beaver Colonizationsupporting
confidence: 63%
“…Some of these studies also documented the increase in beaver populations that accompanied these vegetation changes (table 2). As beaver colonize and build dams, they contribute to the vegetation recovery process (Fesenmyer et al 2018).…”
Section: A B C Dmentioning
confidence: 99%
“…In contrast, less documented are NDVI responses to climate variability, in humid and temperate regions, where water stress is an emerging threat (Gómez-Gener et al, 2020;Masante et al, 2018). In addition, previous studies have suggested that the major climatic factors affecting NDVI response may vary among climatic regions, riparian vegetation structure and management type (Huntington et al, 2016;Fesenmyer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how groundwater dependent areas located within rangelands are affected by various management techniques is crucial to conservation. Their importance in arid and semi-arid ecosystems is generally disproportionate to their overall size [1,2]. Riparian areas boost landscape biodiversity [3], filter water [4], provide forage and water for livestock [5], and serve as suitable seasonal and year-round habitat for a wide variety of key taxa [6,7].…”
Section: Introductionmentioning
confidence: 99%